2022
DOI: 10.3390/ijms23084312
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Dyslipidemia Synergistically Exacerbate Psoriatic Skin Inflammation

Abstract: Patients with psoriasis are frequently complicated with metabolic syndrome; however, it is not fully understood how obesity and dyslipidemia contribute to the pathogenesis of psoriasis. To investigate the mechanisms by which obesity and dyslipidemia exacerbate psoriasis using murine models and neonatal human epidermal keratinocytes (NHEKs), we used wild-type and Apoe-deficient dyslipidemic mice, and administered a high-fat diet for 10 weeks to induce obesity. Imiquimod was applied to the ear for 5 days to indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 58 publications
1
28
0
2
Order By: Relevance
“…Saturated fatty acids intensify the inflammatory response leading to the activation of keratinocytes and macrophages. Palmitic acid has been shown to activate intracellular signaling pathways in epidermal keratinocytes, leading to increased synthesis of CCL20, CXCL8, and IL-1β [ 62 ]. The same processes can also be activated by leptin.…”
Section: Discussionmentioning
confidence: 99%
“…Saturated fatty acids intensify the inflammatory response leading to the activation of keratinocytes and macrophages. Palmitic acid has been shown to activate intracellular signaling pathways in epidermal keratinocytes, leading to increased synthesis of CCL20, CXCL8, and IL-1β [ 62 ]. The same processes can also be activated by leptin.…”
Section: Discussionmentioning
confidence: 99%
“…Many recent studies have confirmed that the production and accumulation of AGEs in diabetic patients are much higher than that in normal people, which is closely related to various complications of diabetes such as diabetic coronary heart disease, diabetic retinopathy, diabetic nephropathy, and diabetic foot. The occurrence of the diabetic foot may be related to the production of glycation end products, which can damage peripheral nerves [ 27 , 28 ], damage arteries [ 29 , 30 ], and cause skin degeneration [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both environmental and genetic factors are involved in the pathophysiology of psoriasis. Common environmental triggers of psoriasis involve bacterial and viral infections, stress, smoking, obesity, and probably diet [ 92 , 93 ]. Therefore, it is not surprising that several studies indicate an altered plasma lipid homeostasis, including S1P, in psoriasis patients.…”
Section: Sphingosine 1-phosphate and Inflammatory Skin Diseasesmentioning
confidence: 99%